2014
DOI: 10.1089/jpm.2013.0427
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of the PleurX Catheter for the Treatment of Malignant Ascites

Abstract: Background: Malignant ascites is a common complication seen in association with various types of neoplastic processes. Due to high recurrence rates, patients may require multiple paracenteses, which have associated complications such as increased risk of bleeding, infection, pain, and volume and electrolyte depletion. Objective: This study evaluated the management of malignant ascites by placement of the PleurXÒ tunneled catheter system at a single center. Methods: This was a retrospective study of 38 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 13 publications
3
42
1
Order By: Relevance
“…4 Timing of placement for malignant ascites is empiric, though usually it is considered after a patient has had at least two prior LVPs. 2,4 Placement may also be considered in patients for whom disease burden makes frequent clinic visits difficult and when postprocedural symptoms, such as discomfort, fatigue, and dizziness, are troublesome. 3,4 The same considerations are relevant for nonmalignant ascites; however, due to survival and infection concerns, many clinicians limit the off-label use for nonmalignant ascites to patients with an anticipated survival of less than two months.…”
Section: Indicationmentioning
confidence: 99%
See 4 more Smart Citations
“…4 Timing of placement for malignant ascites is empiric, though usually it is considered after a patient has had at least two prior LVPs. 2,4 Placement may also be considered in patients for whom disease burden makes frequent clinic visits difficult and when postprocedural symptoms, such as discomfort, fatigue, and dizziness, are troublesome. 3,4 The same considerations are relevant for nonmalignant ascites; however, due to survival and infection concerns, many clinicians limit the off-label use for nonmalignant ascites to patients with an anticipated survival of less than two months.…”
Section: Indicationmentioning
confidence: 99%
“…4,5 Insertion site erythema, bacterial peritonitis, and exudative drainage have been documented; associated superficial infections are often manageable with oral antibiotics. 2,4 Recent studies have shown much lower complication rates with the tunneled indwelling catheters, with 0.12 events per 100 catheter-days, compared with nontunneled catheter systems. Consequently, the use of nontunneled catheter systems for malignant ascites is essentially archaic.…”
Section: Complicationsmentioning
confidence: 99%
See 3 more Smart Citations